Hematopoietic stem cell transplantation for CTLA-4 insufficiency across Europe: A European Society for Blood and Marrow Transplantation Inborn Errors Working Party study - Tsilifis, Christo; Speckmann, Carsten; Lum, Su Han; Fox, Thomas A; Soler, Adriana Margarit; Mozo, Yasmina; Corral, Dolores; Ewins, Anna-Maria; Hague, Rosie; Oikonomopoulou, Christina; Kałwak, Krzysztof; Drabko, Katarzyna; et al. (The Journal of allergy and clinical immunology, 2024)
BACKGROUND: Cytotoxic T-lymphocyte antigen 4 (CTLA-4) insufficiency causes a primary immune regulatory disorder characterized by lymphoproliferation, dysgammaglobulinemia, and multiorgan autoimmunity including cytopenias and colitis. OBJECTIVE: We examined the outcome of hematopoietic stem cell transplantation (HSCT) for CTLA-4 insufficiency and study the impact of pre-HSCT CTLA-4 fusion protein (CTLA-4-Ig) therapy and pre-HSCT immune dysregulation on survival and immunologic outcome. METHODS: This was a retrospective study of HSCT for CTLA-4 insufficiency and 2q33.2-3 deletion from the European Society for Blood and Marrow Transplantation Inborn Errors Working Party. Primary end points were overall survival (OS) and disease- and chronic graft-versus-host disease-free survival (DFS). Secondary end point was immunologic outcome assessed by immune dysregulation disease activity (IDDA) score. RESULTS: Forty patients were included over a 25-year period. Before HSCT, 60% received CTLA-4-Ig, and median (range) IDDA score was 23.3 (3.9-84.0). Median (range) age at HSCT was 14.2 (1.3-56.0) years. Patients received peripheral blood stem cell (58%) or marrow (43%) from a matched unrelated donor (75%), mismatched unrelated donor (12.5%), or matched family donor (12.5%). Median (range) follow-up was 3 (0.6-15) years, and 3-year OS was 76.7% (58-87%) and DFS was 74.4% (54.9-86.0%). At latest follow-up, disease of 28 of 30 surviving patients was in disease-free remission with median IDDA reduction of 16. Probability of OS and DFS was greater in patients with lower disease activity before HSCT (IDDA < 23, P = .002 and P = .006, respectively). CTLA-4-Ig receipt did not influence OS or DFS. Cause of death was transplant related in 7 of 8 patients. CONCLUSION: HSCT is an effective therapy to prevent ongoing disease progression and morbidity, with improving survival rates over time and in patients with lower pre-HSCT disease activity.
Keywords: dospělí; Female; Europe; Infant; dítě; předškolní dítě; CTLA-4; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; antigen CTLA-4; CTLA-4 Antigen; lidé; Hematopoietic Stem Cell Transplantation; abatacept; transplantace hematopoetických kmenových buněk; Evropa; Allogeneic HSCT; Treatment Outcome; retrospektivní studie; Male; kojenec; primary immune regulatory disorder; Child, Preschool; Young Adult; nemoc štěpu proti hostiteli; belatacept; lidé středního věku; Child; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Graft vs Host Disease; Humans